Visualization of the dynamic interaction between nucleosomal histone H3K9 tri-methylation and HP1α chromodomain in living cells. Issue 7 (21st July 2022) - Sasaki, Kazuki; Suzuki, Michihiro; Sonoda, Takeshi; Schneider-Poetsch, Tilman; Ito, Akihiro; Takagi, Motoki; Fujishiro, Shinya; Sohtome, Yoshihiro; Dodo, Kosuke; Umehara, Takashi; Aburatani, Hiroyuki; Shin-ya, Kazuo; et al.
Summary: Histone lysine methylation is an epigenetic mark that can control gene expression. In particular, H3K9me3 contributes to transcriptional repression by regulating chromatin structure. Successful mitotic progression requires correct timing of chromatin structure changes, including epigenetic marks. However, spatiotemporal information on histone modifications in living cells remains limited. In this study, we created an FRET-based probe for live-cell imaging based on the HP1α chromodomain (HP1αCD), which binds to H3K9me3. The probe was incorporated into chromatin and the emission ratio decreased after treatment with histone methyltransferase inhibitors, indicating that it successfully traced dynamic changes in H3K9me3. Upon entry into mitosis, the probe's emission ratio transiently increased with a concomitant increase in H3K9me3, then exhibited a stepwise decrease, probably due to loss of HP1αCD binding caused by phosphorylation of H3S10 and demethylation of H3K9me3. This probe will be a useful tool for detecting dynamic changes in chromatin structure associated with HP1α. Graphical abstract: Highlights: An FRET probe was developed for monitoring the H3K9me3 binding to HP1α chromodomain A newly identified pan-HMT inhibitor, AO-159, reduces H3K9me3 in cells The developed FRET-based probe is incorporated into chromatin The probe response reflects methylation and phosphorylation in H3 during mitosis Abstract : Sasaki et al. develop Hismet-HP1αCD, an FRET-based imaging probe that enables visualization of the dynamic changes in histone H3K9me3 in living cells. They observe a rapid increase in H3K9me3 from G2 to prophase and a decrease in telophase. The probe also detects phosphorylation of H3S10 in prometaphase.